1995
DOI: 10.1021/bi00040a027
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of .alpha.-Lactalbumin with Phosphatidylglycerol. Influence of Protein Binding on the Lipid Phase Transition and Lipid Acyl Chain Mobility

Abstract: The mobility of spin-labeled lipids has been studied in dioleoyl and dimyristoyl phosphatidylglycerol bilayers and in their complexes with alpha-lactalbumin at pH 4.0, by using electron spin resonance (ESR) spectroscopy. The ESR spectra of phosphatidylglycerol spin-labeled at position 5 of the sn-2 chain indicate that association of alpha-lactalbumin with dimyristoyl phosphatidylglycerol bilayers increases the chain mobility at temperatures in the lipid gel phase, restricts the chain mobility at temperatures c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…PC Fluorescence spectroscopy and circular dichroism Lala et al, 1995. DOPG and DMPG Electron spin resonance spectroscopy Montich & Marsh, 1995. a Abbreviations: DMPC, dimyristoylphosphatidylcholine; DMPG, dimyristoylphosphatidylglycerol; DOPG, 1,2-dioleylphosphatidylglycerol; DPPC, dipalmitoylphosphatidylcholine; DPPG, dipalmitoylphosphatidylglycerol; DSPS: 1,2-distearoyl-sn-glycero-3-[phospho-L-serine]; EPA, egg phosphatidic acid; EPC, egg phosphatidylcholine; EPS, egg phosphatidylserine; EYL, egg yolk lecithin; EYPC, egg yolk phosphatidylcholine; NBD-PE, N-(7-nitro-2,1,3-benzoxadiazol-4-yl) phosphatidylethanolamine; PBPS, porcine brain phosphatidylserine; PC, phosphatidylcholine; in solution, the protein was shown to be able to insert itself into the liquid condensed monolayer at an initial surface pressure of 39 AE 0.7 mN m À1 whereas in the presence of a Ca 2þ chelating agent, such as EDTA, the surface pressure was greater. These results show clearly the influence of the protein stability on its capacity of insertion into lipid monolayers.…”
Section: Interaction Of A-la With Lipid Monolayersmentioning
confidence: 99%
See 4 more Smart Citations
“…PC Fluorescence spectroscopy and circular dichroism Lala et al, 1995. DOPG and DMPG Electron spin resonance spectroscopy Montich & Marsh, 1995. a Abbreviations: DMPC, dimyristoylphosphatidylcholine; DMPG, dimyristoylphosphatidylglycerol; DOPG, 1,2-dioleylphosphatidylglycerol; DPPC, dipalmitoylphosphatidylcholine; DPPG, dipalmitoylphosphatidylglycerol; DSPS: 1,2-distearoyl-sn-glycero-3-[phospho-L-serine]; EPA, egg phosphatidic acid; EPC, egg phosphatidylcholine; EPS, egg phosphatidylserine; EYL, egg yolk lecithin; EYPC, egg yolk phosphatidylcholine; NBD-PE, N-(7-nitro-2,1,3-benzoxadiazol-4-yl) phosphatidylethanolamine; PBPS, porcine brain phosphatidylserine; PC, phosphatidylcholine; in solution, the protein was shown to be able to insert itself into the liquid condensed monolayer at an initial surface pressure of 39 AE 0.7 mN m À1 whereas in the presence of a Ca 2þ chelating agent, such as EDTA, the surface pressure was greater. These results show clearly the influence of the protein stability on its capacity of insertion into lipid monolayers.…”
Section: Interaction Of A-la With Lipid Monolayersmentioning
confidence: 99%
“…The hydrophobic patches exposed on the a-LA molten globule surface are considered of key importance for the insertion of the protein into membranes (Chaudhuri et al, 2004;Lala et al, 1995;Montich & Marsh, 1995). In comparison with the apo form of the protein, it has been indicated that this latter inserts into lipid bilayer at slower kinetic than molten globule state (Chaudhuri et al, 2004).…”
Section: Effect Of Lipid Interaction On A-la Structurementioning
confidence: 99%
See 3 more Smart Citations